2018
DOI: 10.1038/s41598-018-25271-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Elongation Factor GreA Plays a Key Role in Cellular Invasion and Virulence of Francisella tularensis subsp. novicida

Abstract: Francisella tularensis is a facultative intracellular Gram-negative bacterium that causes the zoonotic disease tularemia. We identified the transcription elongation factor GreA as a virulence factor in our previous study, but its role was not defined. Here, we investigate the effects of the inactivation of the greA gene, generating a greA mutant of F. tularensis subsp. novicida. Inactivation of greA impaired the bacterial invasion into and growth within host cells, and subsequently virulence in mouse infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…It is known that GreA influences not only cellular invasion but also replication in Francisella tularensis subsp. Novicida (Cui et al, 2018) and Salmonella typhimurium (Gaviria-Cantin et al, 2017). Our data also revealed that greA deletion caused a slight reduction of intracellular fitness in M. tuberculosis H37Rv, suggesting that GreA is required for the maintenance of intracellular survival of M. tuberculosis.…”
Section: Transcription Regulation By the M Smegmatis Transcription Esupporting
confidence: 62%
“…It is known that GreA influences not only cellular invasion but also replication in Francisella tularensis subsp. Novicida (Cui et al, 2018) and Salmonella typhimurium (Gaviria-Cantin et al, 2017). Our data also revealed that greA deletion caused a slight reduction of intracellular fitness in M. tuberculosis H37Rv, suggesting that GreA is required for the maintenance of intracellular survival of M. tuberculosis.…”
Section: Transcription Regulation By the M Smegmatis Transcription Esupporting
confidence: 62%
“…In F. tularensis , GreA was found to be required for invasion and intracellular growth of bacteria. Cui et al (2018) also observed suppression of virulence of the greA mutant in mouse model. Transcriptomics analysis of the greA mutant revealed down-regulation of various genes responsible for virulence.…”
Section: Discussionmentioning
confidence: 75%
“…GreA has been found to have roles in affecting functions of virulence gene expression in the pathogen Francisella tularensis subsp. Novicida ( Cui et al, 2018 ). In F. tularensis , GreA was found to be required for invasion and intracellular growth of bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if the genes in the operon were co-transcribed, the intergenic regions of genes were amplified by RT-PCR [27]. The RNA of the parental strain was extracted and cDNA was synthesized by reverse transcription using the method descibed before.…”
Section: Methodsmentioning
confidence: 99%